Introduction: Ciphering and Ruling Modern China’s Population - Bréard, Andrea; Christ, Stefan (Journal of the European Association for Chinese Studies, 2025)
The special issue “Ciphering and Ruling Modern China’s Population” focuses on the increasing efforts to quantify the Chinese population beginning in the twentieth century. The introduction explains how it does not understand numbers as neutral entities reflecting objective facts but as cyphers that encode hidden realities and emerge from concrete historical contexts. Furthermore, it summarises the four contributions to the special issue: Drawing on approaches from intellectual and conceptual history as well as the sociology of science, they examine Liang Qichao’s early demand for statistics, attempts to quantify China’s Muslim population, Sun Yat-sen’s evolving obsession with the “400 million Chinese”, and the surprising wealth of statistical production in warlord-ruled Shanxi province. The authors ask why numbers, and statistical ones in particular, became so alluring and even fetishised, despite those involved in the production and use of the numbers being aware of their imprecision. Why did statistics become a sine qua non for governing China’s population? And how did specific numbers become central political terms? The authors also explore how numbers were used to construct arguments about China’s “population”, “society”, and “people” and how these arguments changed over tim